She-hulk (2022), volume 5 ebook All in. - Rowell, Rainbow (She-Hulk (2022), 2024)
The newest It Couple in comics, She-Hulk and Jack of Hearts, were supposed to be enjoying a romantic getaway in space - but now Jennifer is fighting for her life on a space station orbiting the sun! The intergalactic crime lord Drapurg is looking for payback after She-Hulk thwarted his attempts to destroy Manhattan - and if that weren't bad enough, someone is also out for emotional revenge as well. But is it aimed at Jen or Jack?! Your heart is not ready for this one! First the action will have it pounding in your chest, then the climax will break it! She-Hulk and Jack of Hearts have seen their love blossom over the last two years of storytelling, but do they have a future? Collecting SENSATIONAL SHE-HULK (2023) #6-10.